﻿Development of novel effective agents from 1H-indolylammonium trifluoroacetates effective against conditionally pathogenic microorganisms - Irina S. Stepanenko; Semen A. Yamashkin; Tatyana N. Platkova; Anastasia I. Kiryutina; Ilya N. Sorokvasha (Belgorod National Research University, 2022)
Introduction: The problem of antibiotic resistance of microorganisms is becoming more urgent in the twenty-first century. More and more pathogenic microbes are becoming resistant to two or more antibiotics. This problem has become worse into the COVID-19 pandemic. The search for new compounds with antimicrobial activity is one of the principles for overcoming the antibiotic resistance of microorganisms. Materials and methods: Methods for the preparation, isolation, and identification of salts of 2,3,5-trimethyl-, 1,2,3,5-tetramethyl-, 2,3-dimethyl-5-methoxy-, 5-methoxy-1,2,3-trimethyl-1H-indole-6-amines and trifluoroacetic acid were developed and laboratory microbiological studies of them for antimicrobial activity were carried out. Sensitivity of the test-strains of microorganisms to the new compounds was studied. A method of serial dilutions to determine the minimal inhibitory concentration (MIC) of the compounds under study was used in the study. Results and discussion: The compounds 5-8 showed a pronounced antibacterial activity against the test strains of microorganisms in vitro with MIC from 0.98 µg/mL to 125.0 µg/mL. The prospects for targeted synthesis of biologically active compounds which are derivatives of 1H-indolylamines with a trifluoromethyl group in the molecule were determined, and after additional studies, the compounds 5-8 may find application as water-soluble synthetic antimicrobial agents. Conclusion: The laboratory microbiological screening of showed that they have an antimicrobial effect that exceeds the activity of the reference drug, dioxidine. The presence of molecular mechanisms predicted in silico in the spectrum of biological activity of the studied compounds, such as Pseudolysin inhibitor, Omptin inhibitor, Undecaprenyldiphospho-muramoylpentapeptide beta-N-acetylglucosaminyltransferase inhibitor, UDP-epimerase inhibitor, Bacterial efflux pump inhibitor, suggests the presence of antimicrobial activity against gram-positive and gram-negative microorganisms. Trifluoroacetates 2,3,5-trimethyl-1H-indole-6-ammonium (5), 1,2,3,5-tetramethyl-1H-indole-6-ammonium (6), 2,3-dimethyl-5-methoxy-1H-indole-6-ammonium (7), 1,2,3-trimethyl-5-methoxy-1H-indole-6-ammonium (8), after additional studies, may find application as water-soluble synthetic antimicrobial agents.